Nutritional evaluation of Moringa oleifera Lam. as a substitute for concentrate feed for bengal goat - Sultana, Nasrin (2014)
Insufficient quality feed is a major limiting factor for goat production in many developing countries including Bangladesh. To overcome this problem, maximizing the use of locally available feed resources and locally grown forages is an alternative option. Moringa oleifera tree is a small tree cultivated in many regions in the south Asian countries and is not fully utilized as ruminant feed. Moringa foliage has not been extensively evaluated in terms of nutritional characterization at different cutting intervals and its partial or whole replacement of concentrate in the diets of goats. It contain polyunsaturated fatty acid and has antioxidant activity, however studies on its effects on goat meat quality in Bangladesh have not been done yet. Therefore, the current study was undertaken with the objectives to (i) evaluate the nutritional characteristics of different plant fractions of Moringa oleifera tree harvested at different cutting intervals and (ii) evaluate the growth performance and carcass and meat quality of Black Bengal goats fed diets supplemented with moringa foliage. To achieve these objectives three experiments were conducted In the first experiment, an existing moringa plot at BLRI with 180 trees, of area 201.86 m2 was used. The plot was divided into 12 blocks which size was 16 m2 having 15 plants and the plots were subjected to three regimes of 4, 6 or 8 weeks cutting intervals. The experimental design was a randomized complete block design (RCBD) consisting of three treatments (4, 6 and 8 weeks cutting interval) with four replications. The highest dry matter (DM) content of total foliage (2247.05; 242.83g kg-1 ), leaf (261.26; 247.30g kg-1) and stem (204.10; 197.65g kg-1 ) were found at the 6 and 8 weeks cutting intervals than 4 weeks cutting interval. The CP content of total foliage (214.80 to 216.20g kg-1DM), leaf (256.65 to 261.33g kg-1DM) or stem (81.30 to 88.44 g kg-1DM) did not differ significantly (P>0.05) among the cutting intervals. The ADF (268.30; 268.46 g kg-1DM), NDF (347.11; 369.51g kg-1DM), and ADL (99.89; 109.00 g kg-1DM) content of total foliage was significantly (P< 0.01) lower in 4 and 6 weeks interval respectively than 8 weeks (310.29, 381.77 and 120.36g kg-1DM, respectively) whereas the fiber content in the leaf was similar among the cutting intervals. IVDMD and IVOMD of total foliage were significantly (P<0.05) higher (801.63; 781.05 g kg-1 and 798.07; 785.06g kg-1DM, respectively) in 4 and 6 weeks interval than 8 weeks interval (772.10 and 761.35g kg-1DM, respectively).Data from the present study suggests that moringa foliage and leaf were better quality in terms of nutrient composition, IVDMD and IVOMD at 4 to 6 weeks cutting interval compare to 8 week. In the second experiment, moringa foliage samples were taken according to experiment-1. Samples from four blocks in each treatment were pooled and taken sample for analysis of the experiment. This experiment was arranged in complete randomized design (CRD) to determine the effect of cutting interval on antnutritional compound, anti-oxidant activity and fatty acid profile of moringa foliage. Total phenols (51.86; 43.89 mg tannic acid equivalent g-1DW), tannin (34.90; 43.89 mg tannic acid equivalent g-1DW), and condense tannin (0.23; 0.17 mg catechin equivalent g-1 DW) content of moringa foliage were significantly (P<0.01) higher at 4 and 6 weeks cutting interval than at 8 weeks (29.00, 16.66 and 0.14respectively). Subsequently, the DPPH radical scavenging activity of moringa foliage was significantly (P<0.05) higher (60.06 %) at 4 wks cutting interval than 6 and 8 wks (55.96 and 53.97 % respectively).From the results obtained in the second experiment exposed that moringa foliage was possess higher antioxidant activity at 4 week cutting interval than 6 and 8 week. In the third experiment, a total of thirty growing Black Bengal goats were allocated into five groups with six goats per treatment. The design of the experiment was a completely randomized design (CRD). The rice straw was used as a basal diet at the rate 30% of total feed. Concentrate mixture feed was substituted with moringa foliage at 25, 50, 75 and 100 among remaining 70% diet. The five dietary treatments consisted of varying proportion of moringa foliage (MF) and concentrate (C), T1 (100MF); T2 (75MF:25C); T3 (50MF:50C); T4 (25MF: 75C) and T5 (100C).The duration of feeding and growth trial was 105 days. After completing the feeding trial, digestibility trial was carried out. Then, four animals from each treatment were randomly selected for slaughter to evaluate the carcass and meat quality. The CP and energy content in moringa foliage and concentrate mixture were 19.95 and 20.04 percent and 11.36 and 11.31 MJ kg-1 DM respectively. Average daily live weight gain (67.83, 79.33, 74.33, 71.33 and 67.33 g d-1 respectively for 100M, 75M: 25C, 50C:50C, 25M: 75C and 100C diet) FCR (6.38, 6.30, 6.28, 6.46 and 6.80 respectively for 100M, 75M: 25C, 50C:50C, 25M: 75C and 100C diet), nutrient intake and utilization were not significantly (P>0.05) different among treatments group except ADF intake and digestibility. Carcass weight and dressing percentage was not (P>0.05) influenced by different dietary treatment. Percentage of lean meat as percent of cold carcass weight was significantly (P<0.05) higher in 75M:25C (73.72%) and 100M (72.18%) diet compare to 50M:50C (69.60%), 25M:75C (69.05%) and 100C (69.30%) diets. Similarly, lean:fat was also significantly (P<0.05) higher in 75M:25C (15.01%) and 50M:50C (11.77%) than that of 50M:50C (69.60%), 25M:75C (69.05%) and 100C (69.30%) diets. Lean: fat was increased upto 75% inclusion level of moringa foliage. Intramuscular fat was also increased with increasing level of concentrate feed in diets. Drip loss of longissimus dorsi (LD) muscle and cooking loss of semitendinosus (ST) muscle was found lower (17.32%; 38.98%, respectively) (P<0.05) value in 100M diet and increased with increasing concentrate feed proportion (17.48, 20.22, 20.37 and 20.62% and 40.85, 41.61, 45.59 and 45.38% ,respectively for drip loss and cooking loss followed by 75M:25C, 50M:50C, 25M:75C and 100M diet). Conversely, shear-force (kg) of both muscles was significantly (P<0.05) increased with increasing concentrate feed in diet. Color characteristics in terms of lightness (L*), redness (a*) and hue angle (H°) of longissimus dorsi (LD) muscle was higher (46.29, 12.55 and 44.89, respectively) in 100M diet compare to other diets. Similar trend was observed in semitendinosus (ST) muscle. Moringa foliage was increased the UFA and PUFA in longissimus dorsi (LD) and semitendinosus (ST) muscles compared to that of a complete concentrate diet. Additionally, proportion of polyunsaturated fatty acid and saturated fatty acid increased with increasing level of moringa foliage and proportion omega-6 and omega-3 fatty acid was reduced with increasing level of moringa foliage in the diets. Moringa foliage, which is affluent in the 18:3n-3, is an important device to generate n-3 PUFA in the meat. Malondialdehyde (MDA), a major lipid oxidation substrate in both longissimus dorsi (LD) and semitendinosus (ST) muscles was reduced with increasing supplementation of moringa foliage. The decreasing in lipid peroxidation level in both muscles indicates the role of moringa foliage as an antioxidant that can protect oxidized lipid in muscle The present study reveals goats fed moringa foliage supplemented diets achieved a favorable growth performance and more desirable leaner carcass with higher proportion of meat and lower weight of subcutaneous fat to improve carcass characteristics. Increasing moringa foliage in diet tended to improve meat quality in terms of water holding capacity and color characteristics. Substitution of concentrate with moringa foliage in diet could also decrease the total SFA and increase polyunsaturated fatty acids in chevon would be favorable in improving health and well-being and reducing degenerative diseases in human being. Moreover, moringa foliage has the significant antioxidant potential, therefore, supplemented of moringa foliage in diets to goats could protect products from oxidative deterioration during the postmortem period. The protective effect of moringa foliage may elucidate its extensive use in shelf life of meat. Thus, moringa foliage could be used as a substitute of expensive concentrate feed for goat.